2019
DOI: 10.1111/jvs.12752
|View full text |Cite
|
Sign up to set email alerts
|

Grazing and warming effects on shrub growth and plant species composition in subalpine dry tundra: An experimental approach

Abstract: Questions: Vegetation in the forest-tundra ecotone faces changes in both climate and land-use. While climate warming is an important driver of vegetation growth and composition, herbivory may have opposing effects. In the present study, we experimentally test how removal of sheep herbivory affects the vegetation in an alpine forest-tundra ecotone, and how responses are manifested at higher temperatures. Location: Dovre Mountains, Central Norway. Methods: Shrub growth (height and cover) and ground layer composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 76 publications
1
17
0
Order By: Relevance
“…This reinforces the idea that in some cases, warming may generate new opportunities for people living under cold conditions [64]. While previous studies suggested that overgrazing is one of the major drivers of rangeland degradation [18,65– 70]. Our results only partly supported this assumption, while grazing treatments did have an overall negative effect on plant biomass and percentage cover, the general trend was not significant due to the high variability in plant response among the sites.…”
Section: Discussionsupporting
confidence: 81%
“…This reinforces the idea that in some cases, warming may generate new opportunities for people living under cold conditions [64]. While previous studies suggested that overgrazing is one of the major drivers of rangeland degradation [18,65– 70]. Our results only partly supported this assumption, while grazing treatments did have an overall negative effect on plant biomass and percentage cover, the general trend was not significant due to the high variability in plant response among the sites.…”
Section: Discussionsupporting
confidence: 81%
“…combined with an upward shift of field layer vegetation suggest that the link with the tree layer might become weaker in a warming climate (Camarero et al, , 2006; Batllori et al, , 2009). These contrasting results suggest that vegetation in the forest–tundra ecotone responds in layer‐specific manners to climate warming, possibly moderated by the presence of herbivores (Vuorinen et al, , 2017; Løkken et al, , 2019). In alpine and arctic tundra ecosystems, herbivory is a well‐known driver counteracting effects of climate warming on vegetation (Olofsson et al, , 2009; Speed et al, , 2012; Eskelinen et al, , 2017), that might inhibit the expansion of deciduous woody species, but with low effect on evergreen woody species (Ylänne et al, , 2015; Vowles et al, , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While gradient studies reflect the present environment, they tend to overestimate effects of climate change as a gradient reflects the average environment over a larger timespan and thus is an expression of site history rather than present climate (Elmendorf et al, , 2015). Experiments, on the other hand, yield detailed control over some selected environmental factors, but are prone to artefacts especially when used over longer timespans (De Boeck et al, , 2015; Ettinger et al, , 2019; Løkken et al, , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies report declines in lichen abundance in arctic‐alpine areas (Fraser, Lantz, Olthof, Kokelj, & Sims, ; Løkken, Hofgaard, Dalen, & Hytteborn, ; Maliniemi, Kapfer, Saccone, Skog, & Virtanen, ; Vanneste et al., ; Vuorinen et al., ), often driven by expansion of vascular plants, and in particular shrubs (Cornelissen et al., ; Fraser et al., ; Vanneste et al., ). Whether the negative effects of vascular plants on lichen communities are mediated by expansion of the already established plants within or close to lichen mats, or by colonizing plants from outside, is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies report declines in lichen abundance in arcticalpine areas (Fraser, Lantz, Olthof, Kokelj, & Sims, 2014;Løkken, Hofgaard, Dalen, & Hytteborn, 2019;Maliniemi, Kapfer, Saccone, Skog, & Virtanen, 2018;Vanneste et al, 2017;Vuorinen et al, 2017), often driven by expansion of vascular plants, and in particular shrubs (Cornelissen et al, 2001;Fraser et al, 2014;Vanneste et al, 2017).…”
Section: Introductionmentioning
confidence: 99%